Unwrapping Success: Strategic Insights into Bhansali Associates' Corporate Gifting Mastery - Bhansali, Ronak (ATLAS SkillTech University, 2025)
The internship report,An Insightful Exploratory: Sales and Business Development Internship at Bhansali Associates, is an elaborative narration of how my school summer job went into the overdrive as I assumed a corporate gifting company Bhansali associates' interview in which their experience enriched our understanding. This report summarizes the learning and experiences which I could garner while completing my internship as a part of curriculum requirement for second year MBA from Atlas Skilltech University. They actively participated in different activities — our client operations, logistics management and various market research as well as product development where they joined us during the summer internship. With the guidance of Bansali Associates, I got a thorough understanding about Corporate Gifting and how you have to be in between Client demands Logistical Constraints & Market Expectation. The report went on to cite what a valuable experience this was for me, how it shaped the rest of my professional career and pretty much sealed in all that I had learned in those years about corporate gifting. Through my engagement on facets of strategizing client interactions, managing the supply chain process and understanding market trends I gained a 360-degree view of the industry along with its operational challenge working for one amongst best in class corporate gifting company.
Project Report on Unwrapping Success: Strategic Insights into Bhansali Associates' Corporate Gifting Mastery (2023-2025) Under the Guidance of Prof. Neha Karnik
Keywords: supply chain; Market Expectation; Logistical Constraints; logistics management; operations; product development